2001
DOI: 10.1088/1126-6708/2001/12/022
|View full text |Cite
|
Sign up to set email alerts
|

The M5-brane on K3 and del Pezzo's and multi-loop string amplitudes

Abstract: We study the BPS spectrum of Little String Theory for bound states of M5branes wrapped on six manifold of product topology M 4 ×Σ 2 and the apparence of multi-loop θ-functions in a supersymmetric index calculation. We find a total reconstruction of the gloop heterotic contribution in the case of a double K3 M-theory compactification. Moreover, we consider total wrapping of M5-branes on del Pezzo surfaces B k and, by studying the relevant amplitude, we notice the arising of θ-functions relative to BPS strings o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Since we have shown that the fiber-base duality, which translates to S-duality in the brane setup picture, is part of the enhanced E N f +1 symmetry, it would be also interesting to consider whether there is any relation between this observation and [71] in which the duality between del-Pezzo surfaces and U-dualities was discussed. Our result may also be related to the theta function arising in the BPS spectrum of M5-branes wrapped on del-Pezzo surfaces [72].…”
Section: Discussionmentioning
confidence: 55%
“…Since we have shown that the fiber-base duality, which translates to S-duality in the brane setup picture, is part of the enhanced E N f +1 symmetry, it would be also interesting to consider whether there is any relation between this observation and [71] in which the duality between del-Pezzo surfaces and U-dualities was discussed. Our result may also be related to the theta function arising in the BPS spectrum of M5-branes wrapped on del-Pezzo surfaces [72].…”
Section: Discussionmentioning
confidence: 55%
“…This holomorphically factorizes in chiral times anti-chiral blocks. The M5-brane partition function is extracted as one of such chiral blocks, in the very same way as chiral partition functions are obtained in two-dimensions[22,23,24,25,26]. The explicit form of this partition function is given in terms of a theta function Θ(Z) with suitable characteristics and arguments.…”
mentioning
confidence: 99%
“…The metric ansatz (30) is close to that for the D7-brane solutions [26], but the crucial difference is the appearance of ρ 2 in G (10) φφ . Owing to this explicit coordinate dependence ('the Weyl canonical coordinate'), τ cannot be holomorphic, and the solution does not preserve supersymmetry.…”
Section: Relation To M-theory Dualitymentioning
confidence: 85%
“…In this correspondence, the Weyl group part of the U-duality group is identified with the Cremona isometry W (E k ) for del Pezzo B k [9]. (This duality was discussed from the point of view of Little String Theory supersymmetric indices [10].) The aim of this paper is to examine the correspondence by closely looking the way how the Weyl group is realized in each case.…”
Section: Introductionmentioning
confidence: 99%